Synthesis of all four nucleoside-based beta-amino acids as protected precursors for the synthesis of polyamide-DNA with alternating alpha-amino acid and nucleoside-beta-amino acids - Seema Bagmare; Varada, Manojkumar; Banerjee, Anjan; Kumar, Vaijayanti A. (Tetrahedron, 2013)
A simple approach is described for the synthesis of all four orthogonally protected nucleoside-beta-amino acids from commercially available starting materials. Synthesis of a model tetrameric DNA sequence in 5'-3'direction employing trityl strategy and glycine as alpha-amino acid alternating with nucleoside-beta amino acids is described. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Antisense therapeutics; Neutral DNA analogues; Nucleoside-beta amino acids